2011
DOI: 10.1007/s11109-011-9165-x
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Volunteering: Selection or Causation? Evidence From a 4 Year Panel Study

Abstract: Participation in voluntary associations is often believed to make citizens more trusting of others. This paper reports longitudinal analyses of a time intensive form of participation-volunteering-and generalized social trust using data from three waves of the Giving in the Netherlands Panel Study spanning 4 years (2002)(2003)(2004)(2005)(2006); n = 692) refuting this belief. Trust is relatively stable over a 4 year period (0.73). Changes in volunteering are not related to changes in trust. Trust is higher amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 49 publications
(63 reference statements)
2
77
0
6
Order By: Relevance
“…For example, the individual-level relationship between social ties and volunteering is likely reciprocal as volunteering strengthens existing ties or leads to new acquaintances. But Bekkers (2012) investigated the individual-level relationship between trust and volunteering over time and found that trust leads to volunteering and not vice versa. It seems reasonable to surmise that same would be true at the regional level, where endogeneity, although still possible, is less of a concern.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the individual-level relationship between social ties and volunteering is likely reciprocal as volunteering strengthens existing ties or leads to new acquaintances. But Bekkers (2012) investigated the individual-level relationship between trust and volunteering over time and found that trust leads to volunteering and not vice versa. It seems reasonable to surmise that same would be true at the regional level, where endogeneity, although still possible, is less of a concern.…”
Section: Resultsmentioning
confidence: 99%
“…However, one cannot rule out the reverse causality and the possible existence of a selection effect. This has been shown to exist, for example, for the relationship between social trust (a major aspects stressed by the social capital theory) and participation (Bekkers 2012;Sønderskov 2011;Stolle 1998). …”
Section: Notesmentioning
confidence: 92%
“…While this theoretical conjecture leaves room for optimism with regard to raising social trust, the empirical evidence for the proposition that participation in voluntary organizations furthers trust is sparseespecially when reverse causality (i.e. trust leading to participation) is taken into account (Bekkers 2012;Claibourn and Martin 2000;Stolle 2001;Uslaner 2002;van Ingen and Bekkers 2015). Nannestad (2008, p. 423) eloquently summarizes this in his review of research on social [generalized] trust: ''It seems that most empirical studies have not been kind to the civic society explanation of generalized trust, and that this is true especially for studies addressing endogeneity problems properly.''…”
Section: Introductionmentioning
confidence: 99%